2002
DOI: 10.1093/jurban/79.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Urban Homelessness and Poverty During Economic Prosperity and Welfare Reform: Changes in Self-Reported Comorbidities, Insurance, and Sources for Usual Care, 1995-1997

Abstract: care (78.3% in 1997 vs. 80.2% in 1995, P = .55)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Both measures highlight weak economies that may be more vulnerable to changes in health care access. (24, 25) Race/ethnicity. We considered racial and ethnic minorities using standard Census Bureau measures: non-Hispanic African American, Hispanic, and other non-Hispanic, non-black populations.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Both measures highlight weak economies that may be more vulnerable to changes in health care access. (24, 25) Race/ethnicity. We considered racial and ethnic minorities using standard Census Bureau measures: non-Hispanic African American, Hispanic, and other non-Hispanic, non-black populations.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…O'Toole et al [12] studied the influence of economic prosperity and welfare reform on the condition of homeless people in Pittsburgh, USA. They were not able to benefit from economic growth and showed more medical and mental health comorbidity, required more long-term medication and more frequently had no health insurance.…”
Section: Homeless Individuals In the Societymentioning
confidence: 99%
“…23 More recently, it has been reported that, even in times of economic prosperity and welfare reform, 940% of one cohort of homeless adults lacked health insurance. 24 All of these barriers have the potential for having a negative impact on HBV vaccine coverage for the children and adolescents living in these families.…”
Section: Discussionmentioning
confidence: 99%